Inhibition and Enhancement of Quantized, Interference‐Driven, Ultrafast‐Laser Cleaving, and Intrafilm Ejection with Angle and Polarization Control. Issue 3 (6th February 2018) - Roper, David M.; Ho, Stephen; Haque, Moez; Jha, Prasoon; Herman, Peter R.
Abstract: The combination of optical interference and ultrafast laser interaction within microscale transparent films offers novel high resolution means for nonlinear confinement of dissipated energy to facilitate 3D nanostructuring. This approach relies on the formation of nanoscale (≈40 nm) plasma disks stacked on half‐wavelength spacings, λ/2 n film (film refractive index, n film ), opening directions for intrafilm cleaving and nanostructuring of free‐standing blisters or embedded nanocavities with controllable surface topography. Given a limited number of film‐substrate systems suitable for generating high contrast interference fringes, this paper introduces angle and polarization control to manipulate fringe visibility in SiO x thin‐films (1 µm thickness) with silicon substrates. An enhancement or diminishment of quantized intrafilm processing is definitively demonstrated according to s‐ and p‐polarization states, respectively. Modeling of Gaussian beam walk‐off effects further explores film interference in tight focusing limits, predicting new asymmetry that manipulates intrafilm cleaving morphology. This research opens a path to quantized structuring of previously unsuitable low‐contrast thin‐film systems, while improving the design and control over novel surface and intrafilm morphologies. The development of intrafilm structuring in SiO x thin‐films is relevant to lab‐in‐film opportunities for assessing cell or subcellular species in CMOS‐compatible microelectronics and improving functionality of LED, lab‐on‐a‐chip and MEMS devices. Abstract : Interferometric quantized processing relies on the formation of thin (≈40 nm) nanoscale plasma disks stacked on half‐wavelength spacing, λ/2 n film (film refractive index, n film ), which opens unforeseen directions for intrafilm cleaving and nanostructuring of free‐standing blisters or embedded nanocavities with controllable surface topography. This work explores the influence of angle and polarization control, demonstrating transition between quantized and full film ejection, and exploring Gaussian beam effects on surface topography.